2008
DOI: 10.1007/s00038-008-7062-9
|View full text |Cite
|
Sign up to set email alerts
|

Does perceived safety of light cigarette encourage smokers to smoke more or to inhale more deeply?

Abstract: Government should attempt to reverse the tendency for light smokers to smoke more under the misconception that light cigarettes are relatively safe, and correct the erroneous belief among smokers who wish to quit that smoking light cigarettes is an intermediate stage on the path to quitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Previous research revealed that the smoking of medium or regular, compared to light, cigarette types was associated with higher levels of smoke exposure (Etter and Perneger 2001). Survey studies show that, in particular, male smokers choosing light brands were more likely to intend to quit (Kelbsch et al 2005), and those light smokers who believed that light cigarettes are relatively safe reported a deeper inhalation of smoke (Lee et al 2008). Thus, the choice of light cigarettes might be driven by different mechanisms, reflecting one's intention to reduce health risks and lower nicotine needs.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed that the smoking of medium or regular, compared to light, cigarette types was associated with higher levels of smoke exposure (Etter and Perneger 2001). Survey studies show that, in particular, male smokers choosing light brands were more likely to intend to quit (Kelbsch et al 2005), and those light smokers who believed that light cigarettes are relatively safe reported a deeper inhalation of smoke (Lee et al 2008). Thus, the choice of light cigarettes might be driven by different mechanisms, reflecting one's intention to reduce health risks and lower nicotine needs.…”
Section: Discussionmentioning
confidence: 99%